Act now: The effects of the 2008 Spanish disability reform. (24th June 2019) - Hill, Matthew J.; Silva, Jose I.; Vall Castello, Judit
Abstract: The 2008 reform of the Spanish disability system reduced the benefits for individuals who have a short contributory history relative to their age. It also unintentionally introduced an incentive for individuals to apply for disability in the present. We use a lifecycle model and an empirical analysis to understand the overall impact of the reform. Our baseline estimates suggest that men and women who were affected by the reform were 46% and 22% more likely to be on permanent partial disability following the reform, respectively, and 55% and 46% more likely to be on total disability, respectively.